PSXI-21 Validation of a Method to Determine Dogs' Preference for Flavors. (21st September 2022) - Johnson, Paris M; Kilburn, Logan; Koppel, Kadri; Aldrich, Charles G
Abstract: There is little information regarding dogs' preference for a given flavor, especially in water. Therefore, the objective of this study was to validate the method of using a consumption test to determine the dogs' ability to discriminate water-based flavors. There were three phases of the study to validate the model using water as a flavor carrier. First was to measure position bias, second to evaluate for preference for specific elemental flavors, and third to evaluate the dogs' ability to district by dose. To eliminate confounding variables; salt (salty), dextrose (sweet), citric acid (sour) and MSG (umami) were mixed with tap water to create colorless and odorless test solutions (salt 0.5%, dextrose 4%, citric acid 0.1%, MSG 0.035%), with tap water as the control. For evaluating dose sensitivity, salt waters at increasing levels of concentration (0%, 0.25%, 0.5%, 1%, 2%) were evaluated. In this study, twelve adult Beagle dogs (average age one year) were individually housed. Using a randomized block design, ceramic bowls, labeled A-E, were placed along the back wall of each pen and filled with 400g of the control or test solutions. Bowl position was randomized daily, to account for any position bias; and water disappearance was measured for five days. Data were analyzed using a mixed model (SAS version 9.4, SAS Institute, Inc., Cary, NC) with treatment as a fixed effect and the dog and day as random effects. Of the elemental flavors, sweet was most preferred (average 250.05g/day) with sour and salty (average 96.45g/day and 85.77g /day) least preferred (p <0.05). Regarding dose distinction, a linear decrease (p<0.05) in water disappearance was observed as salt concentration increased. These results suggest that dogs do have the ability to distinct between flavors. It also suggests that dogs do have the ability to discriminate between different doses.